Shift work and job performance. (Monthly Labor Review, 1996)
A report in the 1995 Journal of Applied Psychology (volume 80) by Peter Totterdell, Evelien Spelten, Lawrence Smith, Jane Barton, and Simon Folkard investigates the job performance and well-being of shift workers. The research participants include 61 nurses, half of whom work full-time rotating shifts and half of whom work full-time or part-time night shifts. Findings reveal that the number of rest days improves sleep length, quality of sleep, alertness, calmness, cheerfulness, mood symptoms, and social satisfaction. Recovery from shifts appears to occur with time, and consecutive days of rest appear to be beneficial. Too much rest time may cause difficulty in adjusting to a night routine, however. The authors' guidelines for time parameters based on their research are discussed.